The Plazuela de los Desamparados and its urban-monumental environment: Historical value of the construction of a place - Ravines Casas, Jonathan (2016)
Just over seventy years ago, in what is now known as the patio of the Government Palace, a plazuela (small plaza) existed: the Plazuela of the Helpless. Its importance and history date back to the early decades of the Spanish foundation of the city. This plazuela was the space that first received Limeños from the neighborhood of “those below the bridge”, as well as a place of congregation for the Jesuit order, who also used to teach at the school located next to the Church of the Helpless. The Church of Our Lady of the Helpless and the Arch of the Stone Bridge comprise the plazuela. These elements, of great architectural and heritage value, succumbed alongside the small plaza due to the vicissitudes of fate and modernity. This article intends to be a small remembrance of the missing plazuela and to reflect about the actual state of this space and its possible recovery for the benefit of the city.